(untitled) (Kyiv-Mohyla Law and Politics Journal, 2021)
This article develops the understanding of symbols as a certain type of signs, the meaning of which is established by agreement or habit. There is an opinion that symbols in public discourse are a reflection of values and anti-values of the society, which are formed in the process of mass communication. This article identifies the main features of the characters, including emotional engagement, attachment to a particular act of communication, as well informativeness. The types of meaning are determined, and the mechanism of nomination is explained. The article reveals the concept of semantic competition. M. Edelman’s opinion that value structures can be divided into mono-, bi- and multimodal — depending on the number of values assigned to key symbols. The presidential speeches delivered before the Ukrainian Constitution Day in 2017–2020 were analyzed in this article. Thanks to the content analysis of emotionally colored words, the symbols, which are characteristic for the speeches of P. Poroshenko and V. Zelensky, were identified focusing both on similarities and differences of Ukrainian values and anti-values. This article analyzes the nominations used by speakers to give meaning to key symbols. Aspects of semantic competition of the key symbols are defined here as well. It was revealed that during the tenure of President Poroshenko, other symbols circulated mostly in the Ukrainian public discourse than those during the presidency of V. Zelensky. Among the common key values for both presidents, we can find “Constitution,” “Constitution Day” and “freedom”. There is a semantic competition in their use. Both presidents underline the negative meaning of the term “parliamentary immunity.” Poroshenko expresses the threat using symbols such as “Russian aggressor”, “fifth column,” “corruption,” “Russian Empire” and “war.” On the other hand, V. Zelensky does not use symbols of external threat. It was found that the value structure formed by Poroshenko’s speeches showed signs of bimodality, and the one created by V. Zelensky’s speeches — multimodality.